F Fruit Carving Training to Increase Creativity in MSME Mothers at The Culture Club Makassar: Pelatihan Fruit Carving untuk meningkatkan kreativitas pada Ibu- Ibu Pelaku UMKM di The Culture Club Makassar - Trisnasari, Damayanti; Astuti, Yayuk; Yusrianti, Yusrianti (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2025)
This community service activity aims to improve the creativity of housewives who are SME actors in developing fruit carving skills as a culinary product presentation innovation. The activity was carried out at The Culture Club Makassar using hands-on training methods, demonstrations, and mentoring. A total of 10 participants took part in training covering basic fruit carving techniques, direct practice in creating fruit carving works, and product development discussions. The results showed that participants were able to practice basic fruit carving techniques well, increase creativity in developing product variations, and gain new insights related to culinary business development based on artistic skills. This activity contributes to strengthening the capacity of SMEs to produce value-added products, while opening up opportunities for innovative business development.